Magnetic-Fe/Fe3O4-nanoparticle-bound SN38 as carboxylesterase-cleavable prodrug for the delivery to tumors within monocytes/macrophages - Wang, Hongwang; Shrestha, Tej B.; Basel, Matthew T.; Dani, Raj Kumar; Seo, Gwi-Moon; Balivada, Sivasai; Pyle, Marla M.; Prock, Heidy; Koper, Olga B.; Thapa, Prem S.; Moore, David; Li, Ping; et al. (Beilstein Journal of Nanotechnology, 2012)
The targeted delivery of therapeutics to the tumor site is highly desirable in cancer treatment, because it is capable of minimizing collateral damage. Herein, we report the synthesis of a nanoplatform, which is composed of a 15 ± 1 nm diameter core/shell Fe/Fe3O4 magnetic nanoparticles (MNPs) and the topoisomerase I blocker SN38 bound to the surface of the MNPs via a carboxylesterase cleavable linker. This nanoplatform demonstrated high heating ability (SAR = 522 ± 40 W/g) in an AC-magnetic field. For the purpose of targeted delivery, this nanoplatform was loaded into tumor-homing double-stable RAW264.7 cells (mouse monocyte/macrophage-like cells (Mo/Ma)), which have been engineered to express intracellular carboxylesterase (InCE) upon addition of doxycycline by a Tet-On Advanced system. The nanoplatform was taken up efficiently by these tumor-homing cells. They showed low toxicity even at high nanoplatform concentration. SN38 was released successfully by switching on the Tet-On Advanced system. We have demonstrated that this nanoplatform can be potentially used for thermochemotherapy. We will be able to achieve the following goals: (1) Specifically deliver the SN38 prodrug and magnetic nanoparticles to the cancer site as the payload of tumor-homing double-stable RAW264.7 cells; (2) Release of chemotherapeutic SN38 at the cancer site by means of the self-containing Tet-On Advanced system; (3) Provide localized magnetic hyperthermia to enhance the cancer treatment, both by killing cancer cells through magnetic heating and by activating the immune system.
Keywords: cell-based delivery; chemotherapeutic prodrug; magnetic Fe/Fe3O4 nanoparticles; SN38